The Bachelor of Arts scoping project : executive summary. - Gannaway, Deanne; Trent, Faith; Upton, Hayley; Price, Sarah (Australian Learning and Teaching Council, 2008)
Executive summary report from a project that aimed: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for Arts Faculties.